2018
DOI: 10.1101/401984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progression of recent Mycobacterium tuberculosis exposure to active tuberculosis is a highly heritable complex trait driven by 3q23 in Peruvians

Abstract: Luo et al. genetics study of TB progression Among 1.8 billion people worldwide infected with Mycobacterium tuberculosis, 5-15% are 1 expected to develop active tuberculosis (TB). Approximately half of these will progress 2 to active TB within the first 18 months after infection, presumably because they fail to 3 mount the initial immune response that contains the local bacterial spread. The other half 4 will reactivate their latent infection later in life, likely triggered by a loss of immune 5 competence due … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…It is more likely to be >10, as shown by the data for the infected control simulation, corresponding to a lifetime risk of TB between 40 and 80%. This OR is higher than those reported for the few SNPs identified by genome-wide association studies (GWAS) in TB (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). These 12 GWAS did not detect the effect of P1104A, as they did not report testing a recessive model.…”
Section: Discussioncontrasting
confidence: 56%
“…It is more likely to be >10, as shown by the data for the infected control simulation, corresponding to a lifetime risk of TB between 40 and 80%. This OR is higher than those reported for the few SNPs identified by genome-wide association studies (GWAS) in TB (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). These 12 GWAS did not detect the effect of P1104A, as they did not report testing a recessive model.…”
Section: Discussioncontrasting
confidence: 56%
“…Twin studies have estimated that the narrow sense heritability of susceptibility to TB can be up to 80%, but very few modern estimates have been done and none have focused on sex-stratified heritability estimates (26,39,(59)(60)(61). In our a previous meta-analysis we estimated the polygenic heritability of TB susceptibility on the autosomal chromosomes of the ITHGC data, which ranged from 5-36% (39).…”
Section: Polygenic Heritabilitymentioning
confidence: 99%
“…As these factors do not fully explain the sex bias, we hypothesise that X-linked genes and the process of XCI could further clarify the phenomenon. Seventeen published GWAS have investigated TB susceptibility (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), but only six of these included the X chromosome in their analysis (16,17,20,26,28,35) and only one of the studies focused specifically on the X chromosome (35). Our previous study, in a South African setting, revealed strong sex-specific effects on both the autosome and X chromosome, suggesting that sex-stratified quality control (QC) and association testing should be done when analysing the X chromosome and autosomes (35).…”
Section: Introductionmentioning
confidence: 99%
“…Two‐locus genotype −2,518 macrophage chemoattractant protein CCL2 (OMIM #158105) GG and −1607 matrix metalloproteinase MMP1 (OMIM #120353) 2G/2G has been found to promote the expression of hyperinflammation in response to Mycobacterium tuberc ulosis infection, inducing extensive tissue damage and a severe TB disease (Ganachari, Guio, Zhao, & Flores‐Villanueva, ). Regarding TB progression, some variants located near the enhancer region on chromosome 3q23 also have been found (Luo et al, ). Together with the data obtained from the Peruvian Genome Project and these previous studies, it will be possible to define the origins and distribution of these new polymorphisms associated with transmissible and non‐transmissible diseases in Peru: integrating Population Genomics knowledge to Public Health.…”
Section: Healthcare Services Of Genetics and Genomicsmentioning
confidence: 99%